Digital Crisis Communication in Telkomsel Network Disruption 2026: Conceptual Framework to Restore and Reputation - Arya rizky putranto; Aulia Pitaloka Sri Prasetyo; Akbar Nurfiriyan; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
This study proposes a conceptual framework to analyze digital crisis communication strategies during large-scale telecommunications service outages, using the 2026 Telkomsel network disruption as an empirical illustration. As societal dependence on digital connectivity intensifies, network failures represent significant organizational crises that threaten corporate reputation and stakeholder trust. By synthesizing Situational Crisis Communication Theory (SCCT) and the Social-Mediated Crisis Communication (SMCC) model, this research identifies the causal mechanisms between crisis response strategies, digital communication, and transparency. In the proposed model, crisis response strategy serves as the independent variable, while digital communication acts as a mediating mechanism that shapes how stakeholders interpret organizational messages. Transparency is positioned as a critical moderating factor that reinforces the relationship between response strategies and stakeholder trust, which ultimately determines long-term corporate reputation. The study develops five propositions suggesting that proactive, transparent, and digitally mediated responses are essential for mitigating reputational damage in a high-velocity digital ecosystem. While providing a strategic roadmap for public relations practitioners in the telecommunications sector, this research also calls for future empirical validation through quantitative and comparative studies to test the robustness of the conceptual links across different industrial and cultural contexts.